Do ELF users construe a motion event differently when addressing a native and a non-native speaker? - Piątkowska, Katarzyna; Strugielska, Ariadna (Moderna Språk, 2024)
Previous research (Strugielska & Piątkowska, 2021) on English as a lingua franca (ELF) from the perspective of Talmy’s typological distinction between S- and V-languages has demonstrated that ELF reveals characteristics of both S- and V-languages. In the present paper we extend this research and examine whether ELF users construe a motion event differently when addressing a native speaker and a non-native speaker of English, a context not discussed before (Hall, 2018). Furthermore, the latest research (Montero-Melis, 2021) on motion events encourages investigation into differences in the construal of motion events across speakers of different languages. Basing on the findings of a qualitative pilot study among Polish users of English, we show that in the narratives addressed to both a native and a non-native speaker of English we may detect features typical of S- and V-languages. However, the results reveal that the nature of V-type framing is slightly different in the two types of texts.